Is Crisis Intervention Team (CIT) training evidence-based practice?: a systematic review - Peterson, Jillian (Journal of crime and justice, 2018)
This study reviews 25 empirical research articles that have examined the impact of Crisis Intervention Team (CIT) training over the past 10 years. Overall, little can be said about the effectiveness of CIT training due to varying outcomes, a reliance on self-report data, lack of comparison or control groups, and inadequate follow-up data. Results of this systematic review of 25 studies demonstrated a mix of positive and negative results, and a focus on urban environments. The impact of officer characteristics and community resources on outcomes is unknown. This review indicates that additional research is necessary before CIT training can be considered an evidence-based practice that should be widely implemented. New training protocols that incorporate empirical research and are responsive to the resources in individual agencies and communities may be more effective.